Identification of Luciferin on Europa through Data Science Analysis of Near-Infrared Mapping Spectrometer (NIMS) Data from the Galileo Orbiter - Matheus Ferreira de Melo, Hugo (International Journal of Physical Research, 2024)
In this study, we investigated the potential presence of extraterrestrial life on Europa, one of Jupiter’s moons, by exploring the existence of Luciferin, a bioluminescent molecule. This hypothesis is based on Europa’s subsurface oceans and the geothermal conditions created by gravitational forces from Jupiter, similar to Earth’s hydrothermal vents. We reanalyzed raw data from the Near-Infrared Mapping Spectrometer (NIMS) on the Galileo spacecraft, utilizing advanced machine learning and data processing techniques to enhance data quality. This involved cleaning, preprocessing, and normalizing the multidimensional data to reduce noise and correct errors, ensuring more accurate analysis. Our primary focus was on detecting spectral signals that might indicate Luciferin, particularly in the spectral bands around 560-570nm, which are associated with Luciferin’s strong emission. The results were encouraging, as several points of interest showed spectral intensity consistent with the presence of this molecule. Although these findings are preliminary and require further validation, they offer promising evidence of bioluminescence on Europa. If confirmed, this discovery would significantly impact the fields of astrobiology and space exploration, providing crucial insights into the search for extraterrestrial life.